Design and Simulation of Direct Digital Synthesizer for Wireless Applications - Kushwaha, Monika; Gokhale, U. M. (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Direct Digital Synthesis is an improved method of producing analog waveforms where the generation is done completely in the digital sphere. In this paper, a design is presented for a Direct Digital Synthesizer (DDS) which generates multiple waveforms. The architecture is based on a 32 bit phase accumulator and a look-up table (LUT) as phase to amplitude converter. This design will be simulated in Xilinx. This DDS will offer qualities like fast switching, good frequency resolution and good stability. This DDS can become highly portable if it is designed on a Field Programmable Gate Array (FPGA).